2011
DOI: 10.3109/14767058.2011.633672
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomarkers of oxidative stress and antioxidant capacity in the cord blood of preterm low birth weight neonates

Abstract: Poor fetal growth affects the development of antioxidant defenses of preterm LBW babies, predisposing them to higher oxidative stress, which in turn may partly account for increased morbidity and mortality in these infants. The presence of an association between oxidative stress biomarkers and enzymatic /non-enzymatic antioxidants in the cord blood of preterm LBW neonates suggest that increased oxidative stress may be the result of changes in the levels of certain enzymatic and non-enzymatic antioxidants due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 17 publications
5
46
1
2
Order By: Relevance
“…Recent studies have demonstrated that premature birth is associated with an increased oxidative stress, and damage promoted by reactive oxygen species that are not properly managed by the immature antioxidant systems of preterm babies. [25][26][27][28] This increased level of oxidative stress has been related to the risk for the so called "free radical-related diseases," such as retinopathy, bronchopulmonary dysplasia and, at intestinal level, NEC 29 which are often associated with preterm birth. Interestingly, breast milk from mothers of full-term infants has been found to have a higher antioxidant capacity than that of mothers of preterm babies.…”
Section: Facultative and Strict Anaerobes In Preterm Neonatesmentioning
confidence: 99%
“…Recent studies have demonstrated that premature birth is associated with an increased oxidative stress, and damage promoted by reactive oxygen species that are not properly managed by the immature antioxidant systems of preterm babies. [25][26][27][28] This increased level of oxidative stress has been related to the risk for the so called "free radical-related diseases," such as retinopathy, bronchopulmonary dysplasia and, at intestinal level, NEC 29 which are often associated with preterm birth. Interestingly, breast milk from mothers of full-term infants has been found to have a higher antioxidant capacity than that of mothers of preterm babies.…”
Section: Facultative and Strict Anaerobes In Preterm Neonatesmentioning
confidence: 99%
“…Decrease in TAC has also been noted in SGA babies [22]. Decrease in TAC in the cord blood of preterm low birth weight neonates have also been reported [23]. Correlation analysis revealed that blood level of MDA of both mother and cord blood correlated negatively with birth weight of the neonates.…”
Section: Discussionmentioning
confidence: 79%
“…All these data correspond to recent studies, proposing in vivo oxidative DNA damage (8-oxodG) and lipid peroxidation as biomarkers of oxidative stress in preterm LBW infants [ 32 ] and the relationship between 8-oxodG and lipid peroxidation to adverse birth outcomes due to exposure to PAHs [ 33 ].…”
Section: The Effect Of Air Pollution On Pregnancy Outcomesmentioning
confidence: 99%